Nasal bacterial microbiota during an outbreak of equine herpesvirus 1 at a farm in southern Ontario - Gomez, Diego E. (Can J Vet Res, 2021)
The objective of this study was to investigate the nasal bacterial microbiota of healthy horses and horses infected with equine herpesvirus 1 (EHV-1). The nasal bacterial microbiota of 10 horses infected with EHV-1 and 11 control horses from a farm experiencing an outbreak was characterized using the Illumina MiSeq platform targeting the V4 region of the 16S ribosomal RNA gene. The nasal bacterial microbiota of healthy horses and EHV-1 horses was significantly different in community membership and structure. Horses shedding EHV-1 had lower bacterial richness (P = 0.002), evenness (P = 0.008), and diversity (P = 0.026) than healthy horses. Healthy horses had a higher relative abundance of Firmicutes and Bacteroidetes, but lower Proteobacteria than horses with EHV-1 (P < 0.05). This study provides the basis for generating hypotheses and investigations on the role of bacterial-viral interactions in the health and diseases of adult horses.